2010
DOI: 10.1073/pnas.1004097107
|View full text |Cite
|
Sign up to set email alerts
|

Injectable hydrogel properties influence infarct expansion and extent of postinfarction left ventricular remodeling in an ovine model

Abstract: A recent trend has emerged that involves myocardial injection of biomaterials, containing cells or acellular, following myocardial infarction (MI) to influence the remodeling response through both biological and mechanical effects. Despite the number of different materials injected in these approaches, there has been little investigation into the importance of material properties on therapeutic outcomes. This work focuses on the investigation of injectable hyaluronic acid (MeHA) hydrogels that have tunable mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
273
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(295 citation statements)
references
References 38 publications
(43 reference statements)
16
273
0
Order By: Relevance
“…This study demonstrated that although both materials similarly thickened, or bulked, the infarcted myocardial wall, high MeHA was able to also decrease infarct size and dilation as well as improve function under stress compared to the infarct control. This provides evidence that the mechanical properties of the injectable [61] material are important to consider for attenuating LV remodeling. Studies with tunable injectable materials will broaden the understanding of factors, such as mechanics and degradation that should be regarded to target LV remodeling via bulking agents.…”
Section: Materials Optimization: Comparing Properties and Introducing mentioning
confidence: 80%
See 2 more Smart Citations
“…This study demonstrated that although both materials similarly thickened, or bulked, the infarcted myocardial wall, high MeHA was able to also decrease infarct size and dilation as well as improve function under stress compared to the infarct control. This provides evidence that the mechanical properties of the injectable [61] material are important to consider for attenuating LV remodeling. Studies with tunable injectable materials will broaden the understanding of factors, such as mechanics and degradation that should be regarded to target LV remodeling via bulking agents.…”
Section: Materials Optimization: Comparing Properties and Introducing mentioning
confidence: 80%
“…Improvements with hydrogel injection were attributed to the biological role of HA, which like fibrin has proven to play a large role in wound healing processes. Additional work with engineered HA hydrogels [61] will be discussed in a section below on modulating hydrogel properties.…”
Section: Natural Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural hydrogels for myocardial injection therapies that have been investigated include fi brin, [ 9 ] collagen, [ 10 ] alginate, [ 11 ] Matrigel, [ 12 ] hyaluronic acid, [ 13 ] and chitosan. [ 14 ] These hydrogels can potentially be delivered in combination with cells or drugs, however, they are derived from a natural source and therefore show batch-to-batch differences.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cell loss in the process of aggregate formation and mechanical injury to the cells during injection are still inevitable. Alternatively, biomaterial-assisted cell delivery approaches have been developed in which responsive biomaterials (e.g., thermal or pH-sensitive hydrogel) can be coinjected with the cells in aqueous form at ambient condition and cross-linked in situ in the body to realize gelation and cell encapsulation (16). However, in situ cross-linked biomaterials such as hydrogel do not allow priming of cells, which could facilitate ECM accumulation and cell-cell interactions for construction of the cellular niche in vitro before transplantation, resulting in immediate exposure of the delivered cells to ischemic and inflammatory microenvironment at the lesion sites.…”
mentioning
confidence: 99%